Grapes and Wine 2022
DOI: 10.5772/intechopen.101112
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Decontamination by Pulsed Electric Fields (PEF) in Winemaking

Abstract: Pulsed Electric Fields (PEF) is a non-thermal technique that causes electroporation of cell membranes by applying very short pulses (μs) of a high-intensity electric field (kV/cm). Irreversible electroporation leads to the formation of permanent conductive channels in the cytoplasmic membrane of cells, resulting in the loss of cell viability. This effect is achieved with low energy requirements and minimal deterioration of quality. This chapter reviews the studies hitherto conducted to evaluate the potential o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Among these technologies, PEF is one of the most appropriate for beverages' preservation, as it can be set in continuous operation for industrial-scale production [5,11]. PEF can be used at various stages of vinification for must or wine decontamination through the electroporation of wine spoilage microorganisms, thus reducing SO 2 additions [12,13] (Figure 1). the most appropriate for beverages' preservation, as it can be set in continuous operation for industrial-scale production [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…Among these technologies, PEF is one of the most appropriate for beverages' preservation, as it can be set in continuous operation for industrial-scale production [5,11]. PEF can be used at various stages of vinification for must or wine decontamination through the electroporation of wine spoilage microorganisms, thus reducing SO 2 additions [12,13] (Figure 1). the most appropriate for beverages' preservation, as it can be set in continuous operation for industrial-scale production [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies performed on wine have demonstrated the inactivating capability of PEF against the most common wineassociated microbiota (yeast and bacteria), either in a batch (Puértolas et al, 2009) or in a continuous process (González-Arenzana et al, 2015;2019). Although several studies have been previously conducted on the subject of microbial inactivation in wine by PEF, there is still a lack of fundamental, systematic studies of microbial resistance to PEF that define appropriate PEF process parameters for microbial decontamination in wineries (Delso et al, 2022). Furthermore, most of these studies did not report the SO 2 concentration in wines on which PEF inactivation experiments were performed, although this concentration could have potentially exerted a certain impact on the final lethal outcome.…”
Section: Introductionmentioning
confidence: 99%